A new understanding of the effect of Cr on the corrosion resistance evolution of weathering steel based on big data technology. (30th March 2022) - Yang, Xiaojia; Yang, Ying; Sun, Meihui; Jia, Jinghuan; Cheng, Xuequn; Pei, Zibo; Li, Qing; Xu, Di; Xiao, Kui; Li, Xiaogang
Highlights: Corrosion big data technology was introduced in design of novel weathering steel. Cr-addition increases the risk of localized corrosion of weathering steel. Mechanisms for beneficial and detrimental effect of Cr element was proposed. Abstract: In this work, we studied the effect of Cr element on the corrosion resistance evolution of weathering steel based on corrosion big data technology. It suggested that corrosion big data technology is suitable for evaluation of the effect of microalloying Cr element on the corrosion evolution behavior of weathering steel. New understandings prove that the effect of Cr on the corrosion process is dynamic rather than static, the processes is affected by both of the environmental factors and the electrochemical or chemical reactions in the rust layer. Besides, Cr element has both beneficial effect and detrimental effect on the corrosion resistance of weathering steel. The beneficial effect is that the general corrosion resistance of Cr-additional steel is better than that of Cr-free steel, while the detrimental effect is that localized corrosion is intensified as the increase of Cr content in the Cr-additional steel.